Harry and the Dinosaurs Say 'Raahh!' - Ian Whybrow (United Kingdom Penguin Random House Children's UK, 2003)
Harry's dinosaurs are acting strangely. They're hiding all over the house and refusing to come out. Could it be because today's the day of Harry's dentist appointment? Eventually Harry persuades them to jump in their bucket, but will the dinosaurs behave once they get to the dentist?
Keywords: Read Aloud -- Read Aloud